Optimizing the Special Job Placement Unit for the Effective Absorption of Vocational High School Graduates - Ula, Alhaura' Nabighatul; Estriyanto, Yuyun; Tamrin, AG; Sukatiman, Sukatiman (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study evaluates the effectiveness of the Special Work Placement Unit (SJPU) in Vocational High Schools (VHS) in channeling graduates into the world of work. Using the Systematic Literature Review (SLR) approach and bibliometric analysis with VOSviewer, this study identified trends and gaps in previous research. With the PICO (Problem, Intervention, Comparison, Outcome) step, the main questions asked include the effectiveness of SJPU in distributing graduates and their supporting and inhibiting factors. The results of the study show that SJPU plays an important role in tracer studies, job training, and partnerships with the business/industry world. However, the limitations of management personnel, ineffective communication of alumni, and the incompatibility of graduate competencies with industry needs are still the main challenges. Therefore, the optimization of SJPU needs to be carried out through increased cooperation with industry, the use of digital technology in employment information, and the alignment of the curriculum with the needs of the job market. This strategic recommendation is expected to help vocational education stakeholders in increasing the absorption of VHS graduates and strengthening the role of SJPU as a link between the world of education and the world of work.